Fibronectin-binding nanoparticles for intracellular targeting addressed by B. burgdorferi BBK32 protein fragments - Ranka, Renate; Petrovskis, Ivars; Sominskaya, Irina; Bogans, Janis; Bruvere, Ruta; Akopjana, Inara; Ose, Velta; Timofejeva, Irena; Brangulis, Kalvis; Pumpens, Pauls; Baumanis, Viesturs (Elsevier, 2013)
Virus-like particles (VLPs) are created by the self-assembly of multiple copies of envelope and/or capsid proteins from many viruses, mimicking the conformation of a native virus. Such noninfectious nanostructures are mainly used as antigen-presenting platforms, especially in vaccine research; however, some of them recently were used as scaffolds in biotechnology to produce targeted nanoparticles for intracellular delivery. This study demonstrates the creation of fusion VLPs using hepatitis B core protein-based system maintaining a fibronectin-binding property from B. burgdorferi BBK32 protein, including the evidence of particles’ transmission to BHK-21 target cells via caveolae/rafts endocythosis. These results make this construct to be an attractive model in development of HBc-based nanoparticles for cellular targeting applications and highlights the fragment of B. burgdorferi BBK32 as a novel cellular uptake-promoting peptide.
Keywords: Research Subject Categories::MEDICINE; Research Subject Categories::NATURAL SCIENCES::Biology